Flexural performance of hybrid deck structures constructed using glass textile-reinforced concrete permanent formworks and reinforced concrete - Huy Cuong, Nguyen; Thanh Thuy, Pham Thi; Dinh Loc, Mai (Journal of Transportation Science and Technology, 2024)
The integration of textile-reinforced concrete (TRC) and reinforced concrete (RC) has recently emerged as a promising strategy for developing hybrid structures. This study investigates the flexural behaviour of a hybrid deck structure comprising a TRC-permanent formwork and RC components. The customisable cross-section of the TRC formwork allows adaptation to specific requirements, and the composite material can be tailored for high load-bearing capacity. The flexural behaviour of TRC-RC hybrid decks was investigated on four specimens through a 4-point bending test on this specific hybrid deck type. The test results highlight the adaptability of the TRC permanent formwork with its customisable cross-section and substantial load-bearing capacity, which is particularly suitable for bridge deck composite structures. The formwork cracking load surpasses the required strength during construction. Additionally, the TRC formwork improves the load-carrying capacity, stiffness, and ductility, acting as a beneficial shear connector between the concrete layers. The hybrid deck specimens displayed minimal fine cracks, indicating enhanced crack resistance, improved serviceability, and reduced crack occurrence. The TRC formwork successfully averted transverse cracks at the interface, ensuring enhanced interfacial bond strength and structural integrity.